Linear and spatial correlation of technology components of sugar cane with organic carbon an oxisol in Rio Brilhante, MS - Montanari, Rafael [UNESP]; Oliveira Honorato, Max Alexandre; Silva, Arthur Pereira da [UNESP]; Lima, Elizeu de Souza [UNESP]; Correa, Adriany Rodrigues [UNESP]; Pereira Pellin, Douglas Martins; Santana da Silva, Evelize Nayara (Univ Fed Grande Dourados, 2015)
The sugar cane (Saccharum spp) has become one of the most economically important crops worldwide. This fact can be attributed to its multiple use, which made while the Brazilian economy to grow more rapidly, also raises speculation and doubt regarding its cultivation. The study aimed to evaluate the effect of intensive cultivation area, about some technological components of cane sugar correlated with soil chemical properties for the layers 0.00-0.20 and 0.20-0.40 m. The experiment was conducted at ETH Bioenergy Eldorado Plant located in the Municipality of Rio Brilhante, with a total of 80 samples all georeferenced. The technological components were assessed: total recoverable sugars (TRS), expressed in kg t(-1), soluble solids (SS), sucrose in juice (SJ), apparent purity (AP) and fiber (FIB), expressed in %, as soil attributes were: carbon stock (EC) and organic carbon (OC). Thus, to obtain maximum productivity, searched for variety, the ideal plant population is 14 plants per meter. The organic carbon content and its stock, revealed as potentially suitable attributes to define two zones specific soil management. In future work focused on precision agriculture, employing the same soil properties and plant those in this study, the recommended ranges should be between 119 and 922 m.
Keywords: precision agriculture; geoestatistics; soil management soil; Saccharum spp.